Analisis Tari Piring Kreasi Sanggar Syofyani Dalam Studi Kasus Musik Iringan Tari - Ahmad Teguh Santoso; Wimbrayardi Wimbrayardi (FBS Universitas Negeri Padang, 2019)
The purpose of this study is to describe results of the analysis of creative Piring Dance at Syofyani's studio in the Case Study of Dance Accompaniment which is viewed from the relationship of the dance movements to the music rhythm. This type of research was qualitative research with using a content analysis approach. The instrument of this research was the researcher and it was assisted by supporting instruments such as stationery, camera and laptop. The types of data used were primary and secondary data. Techniques of data collection were conducted by doing library research, observation, interviews and documentation. The steps to analyze data were done by collecting data, listening to audio recording, playing music, transcribing and analyzing scores. The result shows that music and Piring dance is made based on